Analisis Peran Kepemimpinan Transformasional Dalam Mengelola Perubahan Di Industri 5.0 - Surya Sevi Wijayanna (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Abstract. Industry 5.0 brings profound changes through advanced technologies such as artificial intelligence, robotics, IoT, and Big Data. This research explores the crucial role of transformational leadership in addressing these changes. Case studies in various Industry 5.0 companies are used to collect data through interviews, observations, and document analysis. The findings indicate that transformational leadership plays a crucial role in facilitating the adoption of new technologies, accelerating the change process, and achieving organizational transformation goals. Practical implications highlight the need for developing transformational leadership skills to address challenges and opportunities in this Industry 5.0 era. Organizations need to invest in developing visionary leadership, focused on employee development, and capable of creating innovative and adaptive work environments. This research contributes to understanding the important role of transformational leadership in managing change in the Industry 5.0 era.